Emergent Strategy from Spontaneous Anger: Crowd Dynamics in the First 48 Hours of the Ferguson Shooting - Kudesia, Ravi S. (Organization Science, 2021)
The fatal August 9, 2014, officer-involved shooting of a Black teenager in Ferguson, Missouri, sparked a series of local protests that culminated in a national social movement: Black Lives Matter. In this study, through a minute-by-minute analysis of crowd dynamics, I find that the eventual social movement strategy emerged from spontaneous acts of anger in protest crowds within the first 48 hours of the shooting. This finding is surprising in light of social movement scholarship, in which strategy is thought to follow from rationality and decision making within formal organizations, not emotionality and spontaneous action within informal crowds. By coupling a historical analysis of protest and policing practices with a comparison of prominent theories of crowds, emotion, and strategy, I theorize how strategy can emerge from spontaneous acts of anger as part of a distributed sensemaking process in crowds, rather than conflating strategy with rationality and deliberate planning in organizations. Taken in sum, this study challenges prevailing ideas about the wisdom of crowds and exemplifies the immanent potential for change, in which our seemingly “micro” actions are not trivial but can influence even the most “macro” of strategic outcomes.